Agricultural literacy among junior high school students in Indramayu - Syahrul Bachtiar; Rusman Rusman; Dwi Ajni Shafarwati (Himpunan Pengembang Kurikulum Indonesia, 2025)
Indramayu Regency as one of the leading agrarian regions in West Java with the highest rice production, demonstrates a strong interconnection between its community and the agricultural sector. However, challenges related to farmer regeneration and negative perceptions of agriculture pose a threat to the sector's sustainability. Agricultural literacy is a crucial factor in enhancing junior high school students’ understanding of agriculture’s roles in social, economic, and environmental contexts. This research aims to examine the urgency of agricultural literacy among junior high school students in Indramayu Regency. A descriptive quantitative method was employed, utilizing a survey with a standardized test adapted from the Judd-Murray Agricultural Literacy Instrument (JMALI). The research was conducted at a junior high school in Indramayu, which was selected for its representation of the local farming community, as most students come from farming families and the school is situated in an agricultural area. Purposive random sampling was used to select participants. The results indicate that students’ agricultural literacy is generally low, with most students lacking knowledge, particularly regarding the connections between agriculture and economic, social, health, cultural, and environmental aspects. The study also discusses approaches to improve students’ agricultural literacy by integrating agricultural concepts into curriculum development. Abstrak Kabupaten Indramayu merupakan salah satu daerah agraris dengan produksi padi tertinggi di Jawa Barat, memiliki keterkaitan erat antara masyarakat dan sektor pertanian. Namun, tantangan regenerasi petani dan persepsi negatif terhadap pertanian mengancam keberlanjutan sektor ini. Literasi pertanian menjadi kunci penting untuk meningkatkan pemahaman siswa SMP tentang peran pertanian dalam aspek sosial, ekonomi, dan lingkungan. Penelitian ini bertujuan untuk melihat urgensi literasi pertanian pada siswa sekolah menengah pertama di kabupaten Indramayu. Metode yang digunakan adalah kuantitatif deskriptif dengan menggunakan survey. Instrumen yang digunakan untuk pengumpulan data adalah tes standar yang diadaptasi dari Instrumen Literasi Pertanian Judd-Murray (JMALI). Lokasi penelitian ini disalah satu SMP di Indramayu. Sekolah ini dipilih karena dianggap merepresentasikan masyarakat Indramayu yang bermata pencaharian sebagai petani, karena letak geografisnya berada di wilayah pertanian dan mayoritas peserta didik adalah keluarga petani (family farmer). Teknik sampeling penelitian ini menggunakan purposive random sampling. Hasil uji pemahaman siswa terkait literasi pertanian menunjukan dikategori Rendah, Mayoritas siswa belum mengenal literasi pertanian terutama yang berkenaan dengan hubungan pertanian dengan ekonomi, sosial, kesehatan, budaya dan lingkungan. Dalam penelitian ini juga membahas terkait pendekatan untuk meningkatkan pemahaman siswa terkait literasi pertanian dengan mengintegrasikannya ke dalam pengembangan kurikulum. Keywords: kurikulum integrasi; literasi pertanian; pembangunan berkelanjutan